Evaluation and Ranking of Universities in Tehran with the Emphasis on the State of the University Ranking Systems - Omidifar Reza; Ali Reza Ghalee; Mohammad Hasani; Mir Najaf Mousavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The aim of this study was to evaluate and rank the universities in Tehran with the emphasis on the state of the university ranking systems. This is an applied and descriptive-analytic study. The statistical population of the study consisted of 383 students from Tehran public universities selected through random sampling. With respect to data collection, a questionnaire, with the Cronbach reliability index of 0.951, was utilized. To analyze the data,  TOPSIS and SPSS were used. The results showed that in terms of non-cognitive characteristics, there were significant differences across universities of Tehran in. Moreover, each method of ranking drew on different benchmarks and indices for rankig which are different from one another.  The results also showed that the integrative indices used in University  of Tehran, Sharif University of Technology,  and Tarbiat Modares ranked them first, second,  and third, respectively in terms of measured indices.